Longitudinal impact of postmastectomy radiotherapy on arm lymphedema in patients with breast cancer: An analysis of serial changes in arm volume measured by infrared optoelectronic volumetry. (May 2021) - Kim, Nalee; Kim, Haeyoung; Hwang, Ji Hye; Park, Won; Cho, Won Kyung; Yeo, Seung Mi; Lee, Hyebin; Lee, Sei Kyung
Highlights: Based on temporal changes of arm lymphedema measurement, persistent severe lymphedema was observed in 21.5% of patients diagnosed with lymphedema after total mastectomy. Postmastectomy radiation therapy (PMRT) was significantly associated with consistent increase in affected arm volume assessed by infrared optoelectronic volumetry. Regional node irradiation, not chest wall irradiation alone, significantly increased the incidence of persistent severe lymphedema. In addition to PMRT, arm volume at diagnosis of lymphedema, cellulitis, compliance to physical therapy was related to the risk of persistent severe lymphedema. Abstract: Background and purpose: This study was conducted to evaluate the longitudinal impact of postmastectomy radiation therapy (PMRT) on persistent severe lymphedema (PSL) using arm volume measurements by an infrared optoelectronic volumetry. Materials and methods: Of the patients who underwent mastectomy between 2008 and 2016, we included 330 patients with secondary arm lymphedema. Percentage of excessive volume (PEV) of the arm were serially assessed using an optoelectronic volumetry 1, 3, 6, 12, 18, 24, 36, and 48 months after the lymphedema diagnosis (Tlymh_Dx ). We defined PSL as 2 or more episodes of PEV ≥ 20%. Risk factors for PSL were evaluated using stepwise regression analyses. Results: Patients who received PMRT ( n  = 202, 61.2%) were more likely to have larger extent of axillary node dissection (AND), and frequent stage II/III lymphedema at Tlymh_Dx than those who did not receive PMRT ( p  < 0.001). With a median follow-up of 72.5 months, PSL occurred in 71 (21.5%) patients. Patients with PSL were more frequently treated with AND of ≥ 20 nodes without reconstruction, had advanced lymphedema stage and higher PEV at Tlymh_Dx, and more frequent events of cellulitis compared to those without PSL. The risk of developing PSL was significantly associated with PMRT with regional node irradiation (RNI), AND of ≥20 nodes, lymphedema stage, and PEV at Tlymh_Dx, cellulitis, and compliance with physical therapy. Conclusion: PMRT, especially RNI, was associated with a consistent increase in PEV in patients with arm lymphedema. Therefore, timely physical therapy is necessary for this patient population.